Gut Microbiota Co-microevolution with Selection for Host Humoral Immunity - Yang, Lingyu; Liu, Shuyun; Ding, Jinmei; Dai, Ronghua; He, Chuan; Xu, Ke; Honaker, Christa F.; Zhang, Yan; Siegel, Paul; Meng, He (Frontiers in Microbiology, 2017)
To explore coevolution between the gut microbiota and the humoral immune system of the host, we used chickens as the model organism. The host populations were two lines (HAS and LAS) developed from a common founder that had undergone 40 generations of divergent selection for antibody titers to sheep red blood cells (SRBC) and two relaxed sublines (HAR and LAR). Analysis revealed that microevolution of host humoral immunity contributed to the composition of gut microbiota at the taxa level. Relaxing selection enriched some microorganisms whose functions were opposite to host immunity. Particularly, Ruminococcaceae and Oscillospira enriched in high antibody relaxed (HAR) and contributed to reduction in antibody response, while Lactobacillus increased in low antibody relaxed (LAR) and elevated the antibody response. Microbial functional analysis showed that alterations were involved in pathways relating to the immune system and infectious diseases. Our findings demonstrated co-microevolution relationships of host-microbiota and that gut microorganisms influenced host immunity.